The role of animation in developing intellectual awareness of primary school students (Journal of the College of Basic Education, 2022)
The research tagged "The Role of Animation in Developing Intellectual Awareness for Primary School Students" includes in its methodological framework the research problem, which revolves around a very important issue related to the role of animation in developing intellectual awareness, especially with the wide spread of animation in various means of communication and the positives and negatives it carries. Accordingly, the hypothetical question was determined as a summary of the research problem as follows: What is the role of animation films in developing the awareness of primary school students?Then the researcher defines the goal of the research, its limits, and presents in defining the terms a set of definitions and defines them procedurally.